2004
DOI: 10.1099/jmm.0.05337-0
|View full text |Cite
|
Sign up to set email alerts
|

New genomospecies related to Borrelia valaisiana, isolated from mammals in Okinawa archipelago, Japan

Abstract: In 2000 and 2001, a survey was conducted of Borrelia isolated from various mammals in the southernmost islands of Japan, including Okinawa (main island), Izena, Iriomote and Ishigaki. Isolates obtained from the ear tissues of Suncus murinus (10 isolates), Mus calori (four isolates), Rattus norvegicus (one isolate) and Crocidura watasei (one isolate), were characterized by RFLP of the 5S-23S rDNA intergenic spacer and sequence analysis of the intergenic spacer, 16S rDNA and flagellin gene. While these isolates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 36 publications
(39 reference statements)
2
30
0
Order By: Relevance
“…At present, B. valaisiana-related sp. is known to be widely distributed in the Far Eastern countries of Korea, Taiwan and China [23,24,26,28]. In addition to the above reports, Chu et al also reported that multilocus sequence analysis suggested that the novel Borreila sp.…”
mentioning
confidence: 89%
See 3 more Smart Citations
“…At present, B. valaisiana-related sp. is known to be widely distributed in the Far Eastern countries of Korea, Taiwan and China [23,24,26,28]. In addition to the above reports, Chu et al also reported that multilocus sequence analysis suggested that the novel Borreila sp.…”
mentioning
confidence: 89%
“…Before this study, rodents and shrews were estimated to be reservoir hosts, because B. valaisianarelated sp. strains were isolated from skin specimens of wild small mammals [24,42]. In this study, some of the B. valaisiana-related sp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Borrelia strains belonging to the B. valaisiana-related group have been isolated from A. agraricus rodents, N. confucianus rodents and I. granulatus ticks in Zhejiang province of mainland China (Masuzawa et al, 2001), from Ixodes nipponensis ticks in Korea (Masuzawa et al, 1999), and from I. granulatus ticks and a variety of rodents in Japan (Masuzawa et al, 2004). At first, these Borrelia spirochaetes were tentatively considered to belong to the B. afzelii-related group on the basis of 16S rDNA gene sequences (Kee et al, 1996).…”
Section: B Burgdorferi Sl Prevalence In Rodentsmentioning
confidence: 99%